Democracy and authoritarianism in the Arab world - Pratt, Nicola 1970- (Rienner, 2007)
Reconsidering democratization in the Arab world -- The normalization of authoritarianism -- Challenges to authoritarianism -- Authoritarianism renewed -- The politics of democratization -- Transnational links and democratization -- Conclusion